Uses of new sensitivity and DAE solving methods in SMARTMOBILE for verified analysis of mechanical systems - Auer, Ekaterina; Luther, Wolfram (Zielona Góra: Uniwersytet Zielonogórski)
Software for modeling and simulation (MSS) of mechanical systems helps to reduce production costs for industry. Usually, such software relies on (possibly erroneous) finite precision arithmetic and does not take into account uncertainty in the input data. The program SMARTMOBILE enhances the existing MSS MOBILE with verified techniques to provide a guarantee that the obtained results are correct and measure the influence of data uncertainty. In this paper, we outline the main features and functionalities of SMARTMOBILE. In particular, we focus on its use of newly developed methods for sensitivity analysis and DAE solving for several practically relevant mechanical systems.
Keywords: multibody systems; result verification; sensitivity; DAE; uncertainty